Investigation of high load operation of spark-ignited over-expanded Atkinson cycle engine. (15th March 2020) - Yang, Zhuyong; Miganakallu, Niranjan; Miller, Tyler; Bonfochi Vinhaes, Vinicius; Worm, Jeremy; Naber, Jeffrey; Roth, David
Highlights: 1-D simulation of over-expanded Atkinson cycle engine with multi-link mechanism. Atkinson cycle engine benefits from its lower knock propensity and over-expansion. Atkinson cycle engine operates stoichiometric air-fuel ratio at high load conditions. Energy losses of baseline engine and Atkinson cycle engine are compared. Efficiency for Atkinson cycle engine is relatively 27% higher than baseline engine. Abstract: A boosted spark-ignited over-expanded engine was investigated through 1-D engine simulation. A conventional 4-stroke turbocharged spark-ignited engine with 10.5:1 compression ratio (CR) was selected as the baseline engine. The Atkinson cycle engine model was developed and calibrated based on a multi-link mechanism. The compression ratio (CR) and over expansion ratio (OER) of the Atkinson cycle engine are 10.5 and 1.5, respectively. Two speed and load conditions of 1500 rpm, 13 bar net indicated mean effective pressure (IMEPnet) and 3500 rpm, 20 bar IMEPnet with valve timing optimization were investigated. Results depict that the increase in indicated efficiency of Atkinson cycle engine was from both portions of over-expansion and non-over-expansion portion of the cycle. Atkinson cycle engine benefits from lower knock propensity and lower exhaust temperature. At 1500 rpm, 13 bar IMEPnet, the simulation results indicated that energy loss due to combustion phasing was 2.1% and 0.4% for baseline and Atkinson cycle engine. Net indicated efficiency of Atkinson cycle engine was increased by 16%. At 3500 rpm, 20 bar IMEPnet, baseline engine was operated at knock limited spark timing and fuel enrichment to reduce the turbine-inlet temperature. Net indicated efficiency of optimized Atkinson cycle engine at 3500 rpm 20 bar IMEPnet was higher by 27% in comparison to the optimized baseline engine. The combustion phasing loss was 1.2% and 0.6% for baseline and Atkinson cycle engine, respectively. The energy loss due to fuel enrichment was 6.0% and 1.6% for baseline engine and Atkinson cycle engine, respectively, indicating that the Atkinson cycle engine was beneficial to maximize its efficiency.